Quantitative Study of the differences in Mithocondrium distribution between DENV Infected and Mock Cells (2016)
ABSTRACT: The mithocondria distribution (MD) around nuclei is dynamically changing through clustering, fusion and fission of organelles [1], so the MD takes an appropiated form for each of the different cell functions [2]. Then it is expected that such distribution gets modified when the cell is under viral infection. To study such changes, several videos were taken through a set of live cell imaging experiments on cell cultures expressing fluorescent mithocondria of both: healthy (mock) and infected cells with Dengue Virus (DENV). The fluorescent organelles cluster in regions that shows up to be brighter where the MD is higher, then MD would be extracted from each frame as proportional to the brightness of the picture. Each experiment has follow standard protocols that provide approximately the same initial state for each cell of the same kind (mock or infected). As any studied cell starts from a different pattern of MD around the nuclei, it is expected for each one of those patterns to be equally likely, then the MD density can be approximated as the average of MD in each frame. Each MD has been modeled through a numerical function build as a two dimensional interpolation of the intensity levels, by using a bivariate b-splines method. Each cell has been modeled as an ellipsis, so the MD density function ρ is a function of the distance to the nuclei center r, the angle from major semi axis θ and time t. By carefully looking at ρ(r, θ, t) at fixed θ or fixed r (figure 1), it is clear that the distribution for infected cells has less defined clusters as shown by having more oscillations and lesser distance between peaks and background. Which means a more disorganized structure. This fact can be used to define a classifier for healthy or infected cells [3]. In this work, a proposal of a quantitative tool to measure the order or disorder on the MD is presented.